Factors Influencing the Purchasing Decision of Crystal Guava - Amalia Nur Intan Pratama; Edy Prasetyo; Bambang Mulyatno Setiawan (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2021)
Factors influencing purchasing decision is vital for the product development and market line expansion. This study aimed to analyze consumer’s characteristics and factors influencing the purchasing decision of crystal guava in agrotourism sites owned by the Agricultural Technical Implementing Service Unit in Semarang City. This was a survey study conducted in Cepoko Agrotourism and Purwosari Agrotourism. These locations selected according to several considerations: managed by the Agricultural Technical Implementing Service Unit, Agricultural Board of Semarang City, distributed crystal guava with lower price, and consumer’s high interest in crystal guava that offered in the agrotourism site. A quota sampling technique was employed to select the number of participant required in the study. There were 100 consumers, 67 consumers from Cepoko Agrotourism and 33 consumers from Purwosari Agrotourism. Accidental sampling tecnique then applied to choose the eligible study participants. Descriptive and multiple linear regression analysis enrolled to analyze the study data. Results revealed that the majority of the participant were women, aged between 39 to 45 years old, graduated from senior high school and university (bachelor/diploma), housewives and entrepreneurs, had an average income of IDR 4,500,000/month, and had four family members. Product quality, promotion activity, attitude, and lifestyle identified as factors that affected the purchasing decision. Price, location, and motivation found to be not associated with the consumer’s purchasing decision.